Knowledge, Awareness, and Attitude about Basic Life Support and Emergency Medical Services among Dental Students in Manipal University College Malaysia: A Cross-sectional Study - Ramanathan Ravi; Tanu Nangia; Law Phui Wai; Beh Tjun Qi; Eunice Soo Liang Yi; Lee Xin Jie; Htoo Htoo Kyaw Soe (Journal of South Asian Association of Pediatric Dentistry)
The incidence of cardiovascular disease (CVD) is on the rise among dental patients, leading to an increased risk of developing emergencies. Life-threatening emergencies may not be common to happen in a dental office, however, the likeliness to occur has increased with increased levels of stress. A dental practice is mired in many risks that lead to life-threatening emergencies. Therefore, all dentists must have sufficient knowledge and be versed with the protocols to manage and handle critical situations and emergencies effectively and efficiently, which is life-saving and imperative in a dental setting. Aim: To assess the knowledge, awareness, and attitude among year 3, 4, and 5 dental students regarding basic life support (BLS). Materials and methods: A cross-sectional study was conducted on a sample of dental students (n = 183) in Manipal University College Malaysia (MUCM). Participants completed the Microsoft (MS) form questionnaire, including questions to obtain students’ demographics and questions to evaluate their knowledge, awareness, and attitude of students toward BLS. These questions were then analyzed using the Chi-squared test and Fisher's exact test. Results: All of them (183) completed the survey with a response rate of (100%). Female participant's awareness was higher than the male counterparts, but it did not differ significantly (p-value > 0.05). Year 3 dental students showed a higher awareness level compared to year 4 and 5 dental students (p-value > 0.05). There was a significant difference in the attitude of students toward BLS among year 3, 4, and 5 dental students (p-value < 0.05). Conclusion: Despite students exhibiting a positive attitude toward BLS training, some of them never underwent any formal BLS training. This gap must be bridged immediately to address this issue. Basic life science programs must not only be imparted in the course curriculum but be updated at constant intervals and time.